The Effect of Drying Method on Turmeric Rhizome Simplicia’s Quality - Resa Frafela Rosmi (Indonesian Journal of Multidisciplinary Science, 2021)
Drying is one of the post-harvest processes that plays an important role in the quality of simplicia. Curcuma domestica is a plant that has antimicrobial, antioxidant, antifungal and anti-inflammatory. The objective of this research is to know the effect of drying oven and direct sunlight and to know the drying method which is effective on the quality of Curcuma domestica simplicia. This research is an experimental. Simplicia drying method is oven and direct sunlight. Quality inspection of simplicia include determination of total ash content, acid insoluble ash content, ethanol soluble extract content, water soluble extract content, drying shrinkage, water content and curcumin test with TLC. The results showed that the drying method effected on simplicia quality. Oven drying method gives the best results and is an effective drying method. with a total ash content of 6,6%, acid insoluble ash content of 0,6%, ethanol soluble extract content of 12%, water soluble extract content of 12%, drying shrinkage of 10%, and an Rf value of 0,97.